Chronic conditions and multimorbidity among West African migrants in greater Barcelona, Spain - MacKinnon, Marina J.; Picchio, Camila A.; Nomah, Daniel K.; Segura, Ariadna Rando; Selm, Lena van; Fernández, Emma; Buti, Maria; Lens, Sabela; Forns, Xavier; Rodriguez-Tajes, Sergio; Pamplona, Javier; Lopez, Carmen; et al. (Frontiers in Public Health, 2023)
Objectives This study aimed to report the prevalence and identify potential risk factors of chronic conditions among West African migrants living in the greater Barcelona area, Spain, and explore the relationship between years of residence in Spain and chronic disease burden. Methods This cross-sectional study included 436 adult African migrants who participated in a community-based hepatitis B virus (HBV) screening and vaccination program (HBV-COMSAVA) in the greater Barcelona area from 21 November 2020 to 22 January 2022. Data were analyzed using standard descriptive statistics and bivariable and multivariable logistic regression. Results HBV, non-communicable diseases (NCDs) and metabolic risk factors, and multimorbidity prevalence were 9.17, 20.87, and 4.13%, respectively. Being male or having been previously tested for HBV were associated with higher odds of HBV positivity. Associated risk factors for NCDs and metabolic risk factors included living in Spain for >5 years, being female, and being aged ≥50 years. Conclusion The high prevalence of chronic conditions in migrant populations supports a need for early detection strategies and tailored public health interventions that aim to reduce the disease burden imposed on migrants and on health systems in host countries.